The Efficacy of Denosumab in the Management of a Tibial Paediatric Aneurysmal Bone Cyst Compromised by Rebound Hypercalcaemia - Matthew Harcus; Samantha Aldridge; Adesegun Abudu; Lee Jeys; Senthil Senniappan; Henry Morgan; Barry Pizer (Case Reports in Pediatrics)
Surgery is the main treatment option for patients with aneurysmal bone cyst (ABC). We report our experience of using denosumab as an alternative treatment in a child with a multiply recurrent and unresectable tibial ABC. The efficacy and safety of denosumab in the paediatric population, and in the treatment of ABC, are still to be fully evaluated. We describe a 13-year-old boy with an extensive and aggressive ABC involving the proximal tibia, which had recurred following multiple previous surgeries. The patient had ongoing severe pain, was unable to weight-bear, and was at significant risk of pathological fracture. En bloc resection and embolization were not deemed viable, and a decision to use denosumab was made. He received 17 doses of subcutaneous denosumab (70 mg/m2) over a 27-month period, at increasing dose intervals. His symptoms significantly improved, and bony consolidation was observed within six months of treatment. He was able to walk without protection and fully weight-bear without any pain by 18 months. With an increase to a six-month dosing interval, the patient presented with a severe, symptomatic rebound hypercalcaemia requiring bisphosphonate therapy. This reoccurred on two further occasions. This case adds to the evidence that denosumab is effective in the treatment of ABC in paediatric patients, but there is a risk of rebound hypercalcaemia. Therefore, patient awareness and biochemical monitoring for rebound hypercalcaemia are essential.